Analisis self-regulated learning (srl) berdasarkan perspektif filsafat stoikisme pada mahasiswa PGSD surakarta tahun pertama yang aktif berorganisasi - Muhammad Hanun Hanun Hanifah; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Universitas Sebelas Maret, 2023)
This study analyzes Self-Regulated Learning (SRL) based on the perspective of Stoicism philosophy in first-year Surakarta PGSD students who are active in organizations. The purpose of this research is to analyze the application of SRL based on the perspective of Stoicism in the learning context of students who are active in organizations. The research method used is descriptive qualitative using a Likert scale and interviews as a data collection tool. The results showed that the research subjects were able to apply the principles of Stoicism in SRL aspects such as task analysis, self-motivation belief, self-control, self-observation, self-judgment, and self-reaction. However, subject 1 still requires more attention in some of these aspects. Subject 2, subject 3, and subject 4 have succeeded in applying the principles of Stoicism well in their learning. Overall, the application of the principles of Stoicism helps students develop SRL, motivate themselves, control themselves, and achieve success in learning. This research provides insight into the importance of the Stoicist perspective in the development of independent learning for students who are active in organizations and contribute to the SRL literature in the context of higher education.